Decoding lifespan secrets: the role of the gonad in Caenorhabditis elegans aging - Pires da Silva, Andre; Kelleher, Rhianne; Reynoldson, Luke (Frontiers in Aging, 2024)
The gonad has become a central organ for understanding aging in C. elegans, as removing the proliferating stem cells in the germline results in significant lifespan extension.Similarly, when starvation in late larval stages leads to the quiescence of germline stem cells the adult nematode enters reproductive diapause, associated with an extended lifespan. This review summarizes recent advancements in identifying the mechanisms behind gonadmediated lifespan extension, including comparisons with other nematodes and the role of lipid signaling and transcriptional changes. Given that the gonad also mediates lifespan regulation in other invertebrates and vertebrates, elucidating the underlying mechanisms may help to gain new insights into the mechanisms and evolution of aging.